ANALISIS PENGARUH LITERASI KEUANGAN DAN PENGELOLAAN KEUANGAN TERHADAP KINERJA KEUANGAN PADA USAHA MIKRO DI DESA RAMBAH JAYA - Anisa Meirani; Heffi Christya Rahayu; Hendry Kurniawan (Jurnal Ekonomi Bisnis Kompetif, 2026)
This study aims to analyze the influence of financial literacy and financial management on the financial performance of micro-enterprises. This study uses a quantitative method with a survey approach. Data were obtained through distributing questionnaires to micro-enterprises and analyzed using multiple linear regression analysis. The results show that financial literacy has a positive and significant effect on the financial performance of micro-enterprises. In addition, simultaneously, financial literacy and financial management have a significant effect on the financial performance of micro-enterprises. The coefficient of determination (R Square) value of 0.169 indicates that financial literacy and financial management can explain 16.9% of the financial performance of micro-enterprises, while the remaining 83.1% is influenced by other factors outside this study. Thus, increasing financial literacy and good financial management can improve the financial performance of micro-enterprises.